Sammeln aus Leidenschaft : Die Stiftung Hellmut und Norli Czerny in der Neuen Galerie der Stadt Linz. - Baum, Peter; Czerny, Norli & Hellmut; Reutner, Brigitte; Neue Galerie der Stadt Linz, Linz (Linz : Neue Galerie der Stadt Linz, 2002)
Adrian, Marc ; Aduatz, Friedrich ; Albers, Josef ; Andri, Ferdinand ; Anzinger, Siegfried ; Arakawa, Shusaku ; Auer, Sepp ; Aycock, Alice ; Barfuss, Ina ; Bauer, Karl ; Bazaine, Jean ; Beckmann, Max ; Berg, Werner ; Beuys, Joseph ; Bill, Max ; Birkle, Albert ; Bischof, Peter ; Bischoffshausen, Hans ; Blaas, Franz ; Blank, Michael ; Bloyer, Karl Heinz ; Bohatsch, Erwin ; Bolt, Ronald ; Brandtstätter, Karl ; Braque, Georges ; Braun, Theo ; Brehm, Dietmar ; Brettschuh, Gerald ; Brüning, Peter ; Buchta, Alfred ; Castell, Bertram ; Castellani, Enrico ; Corneille ; Damisch, Gunter ; Danner, Josef ; Decleva, Mario ; Denk, Wolfgang ; Denny, Robyn ; Dobrowsky, Josef ; Dokoupil, Jiri Georg ; Doppler, Horst Maria ; Dorazio, Piero ; Droese, Felix ; Dworak, Peter ; Ecker, Gottfried ; Eckert, Walter ; Ellenrieder, Wolfgang ; Engerth, Eduard von ; Erjautz, Manfred ; Ernst, Max ; Ernst, Wolfgang ; Esterl, Martin ; Estermann, Lorenz ; Fabian, Gottfried ; Felice, Herbert ; Fian, Helmut ; Fieglhuber-Gutscher, Marianne ; Fink, Tone ; Fischer, Johann ; Fleck, Karl Anton ; Fleischmann, Adolf Richard ; Floch, Josef ; Flois, Herbert ; Flora, Paul ; Florian, Maximilian ; Förg, Gunther ; Franta, Hans ; Friedlaender, Johnny ; Fritsch, Marbod ; Frohner, Adolf ; Fruhmann, Johann ; Funder, Martina ; Funke, Helene ; Girke, Raimund ; Glück, Anselm ; Göbel, Heinz ; Götz, Ferdinand ; Gradischnigg, Ernst ; De Groot, Arie ; Gyurko, Stefan ; Harta, Felix Albrecht ; Hartlauer, Fritz ; Hartung, Hans ; Hauenschild, Peter ; Hauer-Fruhmann, Christa ; Hauser, Carry ; Hebenstreit, Manfred ; Hepworth, Barbara ; Herberth, Franz ; Hernandez Pijuan, Juan ; Hessing, Gustav ; Heuer, Christina ; Hikade, Karl ; Hodgkin, Howard ; Hofer, Franz ; Hoflehner, Rudolf ; Hoke, Giselbert ; Hollegha, Wolfgang ; etc.
biog., exponate p. 178-195
Duits
Sammeln aus Leidenschaft : die Stiftung Hellmut und Norli Czerny in der Neue Galerie der Stadt Linz, 27.06 - 23.11.2002
boek